Atypical Presentation of Anti-Phospholipid Antibody Syndrome with Seizure and Atrial Mass - Rajish Sanjit Kumar Shil; Amal Abdallah Al Dhuhoori; Vipin Mughilassery Thomachan; Jamal Ali Teir; Renganathan Radhakrishnan (Case Reports in Medicine)
Anti-phospholipid antibody syndrome (APS) has a broad spectrum of thrombotic and nonthrombotic clinical manifestations. The diagnosis requires a set of clinical criteria of thrombosis along with persistently positive anti-phospholipid antibody tests. In this report, we are presenting a case of APS, who is a 38-year-old male, presented with complains of seizures and found to have stroke, which on further investigation revealed to have been caused possibly from a left atrial mass. Therefore, high index of suspicion is required for the diagnosis of APS in young patients, who present with various neurological and cardiovascular manifestations, mostly secondary to thrombosis.